The Role Of Entrepreneurship Education In Ethnic Chinese Family Business Succession - Arif Isnaini; Dian Tantri; Hevni Rahmania; Moh. Faizin; Ludi Wishnu Wardana; Bagus Shandy Narmaditya (International Journal of Educational Technology and Society, 2024)
Entrepreneurship education is an entrepreneur's effort to have a foundation in entrepreneurship. With entrepreneurial education, an entrepreneur can effectively solve business problems with solutions. This research aims to reveal the role of entrepreneurship education in ethnic Chinese family business succession. The research method was a systematic literature review (SLR) with 576 articles from the Scopus, Emerald, and Sage databases. Then, the articles were identified by inclusion and exclusion with a final number of 2 articles. The research results show that Chinese ethnicity provides opportunities for all their children to continue the family business because all children, both girls and boys, have the same rights in owning the family business. Preparing a successor to an ethnic Chinese family business starts with family entrepreneurship education, guiding potential successors,viting potential candidates to know more about the family business, and involving potential successors in their business activities. The limitation of this research is the lack of articles related to ethnic Chinese family businesses.